VD_FINDINFO Jug / 2020 / 487 vom 10. August 2020 - VD Tribunal cantonal (2020)
DROIT PÉNAL DES MINEURS, VIOLATION DE DOMICILE, PLACEMENT D'ENFANTS, OBSERVATION, IMPUTATION | 186 CP, 32 DPMin, 29 PPMin